2000
DOI: 10.1096/fj.00-0183com
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide inhibits leukocyte‐endothelium interaction in the microcirculation during acute endothelial dysfunction

Abstract: C-peptide is a cleavage product that comes from processing proinsulin to insulin that induces nitric oxide (NO) -mediated vasodilation. NO modulates leukocyte-endothelium interaction. We hypothesized that C-peptide might inhibit leukocyte-endothelium interaction via increased release of endothelial NO. Using intravital microscopy of the rat mesentery, we measured leukocyte-endothelium interactions after administration of C-peptide to the rat. Superfusion of the rat mesentery with either thrombin or L-NAME cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 47 publications
4
81
2
1
Order By: Relevance
“…Therefore, the higher dose of 70 nmol/kg used in this study is likely to induce an approximately five-fold increase in C-peptide plasma level, which has been shown to correct vascular permeability and neuronal dysfunction in diabetic rats [26]. Additionally, Scalia et al demonstrated that this concentration of C-peptide inhibited leucocyte-endothelial interaction during acute endothelial dysfunction [15]. To examine the role of insulin in Cpeptide function, the cremaster muscles of animals treated with C-peptide at either low (7 nmol/kg; n=4) or high (70 nmol/kg; n=4) dose were superfused with insulin solution at a concentration of 100 μU/ml before thrombus induction.…”
Section: Experimental Groups and Protocolmentioning
confidence: 79%
See 1 more Smart Citation
“…Therefore, the higher dose of 70 nmol/kg used in this study is likely to induce an approximately five-fold increase in C-peptide plasma level, which has been shown to correct vascular permeability and neuronal dysfunction in diabetic rats [26]. Additionally, Scalia et al demonstrated that this concentration of C-peptide inhibited leucocyte-endothelial interaction during acute endothelial dysfunction [15]. To examine the role of insulin in Cpeptide function, the cremaster muscles of animals treated with C-peptide at either low (7 nmol/kg; n=4) or high (70 nmol/kg; n=4) dose were superfused with insulin solution at a concentration of 100 μU/ml before thrombus induction.…”
Section: Experimental Groups and Protocolmentioning
confidence: 79%
“…C-peptide further induces endothelial NO-synthetase and, thus, NO production [14]. In addition, it may reduce leucocyte-endothelium interaction through a diminution of endothelial P-selectin and intracellular adhesion molecule type 1 expression [15]. Based on this, insulin deficiency, and thus lack of antiadhesive C-peptide action, could be a causal factor in the development of procoagulative status in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…C-peptide has been shown to display anti-inflammatory activity on endothelial cells exposed to a variety of damaging insults and to be beneficial in endothelial dysfunction during type 1 diabetes [39]. In this regard, pretreatment with C-peptide to rats injected with the inflammatory agents thrombin or N w -nitro-L-arginine methyl ester (L-NAME), which cause acute endothelial dysfunction, resulted in reduced expression of intercellular cell adhesion molecule (ICAM)-1 and P-selectin on the mesenteric microvascular endothelium [28]. As a consequence, the number of rolling, adhering and transmigrated leucocytes also decreased upon C-peptide administration to the animals.…”
Section: Discussionmentioning
confidence: 99%
“…As type 1 diabetes patients typically lack physiological levels of insulin and C-peptide, this is considered an important factor in the pathophysiology of diabetic complications [24][25][26]. C-peptide has been shown to improve endothelial dysfunction and systemic inflammation in several in vivo and in vitro models of inflammation-mediated vascular injury by reducing expression of genes encoding endothelial cell adhesion molecules, inflammatory cytokine production and adherence and transmigration of leucocytes [27][28][29][30]. Although the exact mechanism(s) underlying the antiinflammatory activity of C-peptide is not known, there is evidence that C-peptide affects NF-κB activation [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…A higher C-peptide at baseline and sustained levels at least a year after diagnosis have also shown to be beneficial to reduce the incidences of microvascular complications in T1D and to allow for intensive insulin treatment (to reach HbA1c < 7.5%) together with fewer incidences of severe hypoglycemia (3). Furthermore, there are findings suggesting that C-peptide alters interactions between leukocytes and endothelium by causing a decreased upregulation of cell adhesion molecules and thereby reducing the rate of cell adhesion and migration (4), results that might indicate an inhibitory role of C-peptide in inflammation.…”
mentioning
confidence: 99%